Perundungan di Pesantren: Fenomena Sosial pada Pendidikan Islam: (Studi Pada Pesantren Ulul Albab Tarakan) - M Arfah; Wantini Wantini (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
This research aims to understand the phenomenon of negotiation at the gymnasium, the factors that influence it, its impact, as well as its prevention and management strategies. The research uses a qualitative approach by collecting data through in-depth interviews with centers. The results of the research show that negotiations at the gym can occur because of individual factors, families, social status differences, and mass media. Talks at the gym have a serious psychological impact on the victim, including depression, anxiety, and low self-esteem. In addition, there are negative implications for the educational climate in the training, such as the low participation of centers in educational activities and the emergence of uncertainty. It involves the active role of teachers, caregivers, and parents in identifying signs of negotiation, providing psychological support and support to victims, and involving all pupils in character education that promotes Islamic values such as empathy, tolerance, and justice. It is hoped that the results of this research can be used as a foundation for trainees and related stakeholders to create a safe, harmonious, and dignified educational environment during training.